Pendampingan Penerapan Teknologi Cloud dalam Manajemen Administrasi di Wilayah Jalaluddin Ar-Rumi Pondok Pesantren Nurul Jadid - Faisal; Ahmad Nadif Sanafiri (Yayasan Literasi Altruis Khatulistiwa, 2025)
This community service aims to assist the application of cloud technology in improving administrative management in the Jalaluddin Ar-Rumi Region of Nurul Jadid Islamic Boarding School. The background of this activity shows that the administrative system is still managed manually, resulting in inefficiency and the risk of data loss. The purpose of this program is to introduce a cloud-based system, increase administrative capacity, and build digital literacy among staff. The methods used included assessment, intensive training, system implementation, and evaluation. Key results showed significant improvement in the understanding and use of the cloud platform, with an 80% increase in digital skills. Administrative processes became 40% faster, and an integrated cloud-based administration system was successfully implemented. In conclusion, structured assistance in cloud technology adoption can markedly improve administrative efficiency and support digital transformation in traditional educational institutions